Sosialisasi Dana Desa Melalui Pelaksanaan Pos Gizi dalam Rangka Menanggulangi Masalah Kekurangan Gizi dan Stunting di Desa Polibuhuta Kecamatan Batudaa Kabupaten Gorontalo - Usman Usman (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2023)
Hearth is a service that is carried out at Posyandu and is centered in the Pilobuhuta village office hall by carrying out an activity to prevent malnutrition for young children, breastfeeding mothers, pregnant women and stunting in children by weighing and measuring height which is then identified whether a person is included in the category of malnutrition or not. Nutrition is one of the important components contained in the body that determines a person's level of health. According to the science of nutrition, there are certain levels that can distinguish the health of one individual from another. The quality and quantity of nutritious food determines the state of individual nutrition, because the functioning of the body's components is due to the intake of nutritious food. This service aims to describe nutrition socialization activities as an effort to prevent malnutrition and stunting in the community as well as maintain nutritional status and change the behavior of mothers/families in their respective homes independently, especially families of toddlers, pregnant women, breastfeeding mothers and prevention of stunting in children in rural communities. The method used is the lecture method with the help of animated pictures and videos to facilitate communication and approaches to the community in providing knowledge or education related to the importance of nutrition to health. The results of this activity show that (1) there is an increase in public knowledge about food and nutrition as well as innovations in processed corn (2) the community can practice processing food into nutritious food that is useful for health and prevents stunting